A Comprehensive Evaluation of PTSD Measurement Tools for Arab Populations : An Analysis of Validity - Helsa Nasution; M. Agung Rahmadi; Luthfiah Mawar; Nurzahara Sihombing (Pusat Riset dan Inovasi Nasional, 2025)
This study presents a highly comprehensive meta-analysis of the validity of various Post-Traumatic Stress Disorder (PTSD) measurement instruments that have been implemented within the context of Arab populations. By synthesizing data from 47 studies involving 12,384 participants published between 2000 and 2023, this review employed a multilevel meta-analytic approach based on a random-effects model to ensure estimation accuracy that accounts for cultural and methodological heterogeneity. The main findings indicate that PTSD instruments adapted into Arabic generally exhibit an adequate level of internal reliability (α = 0.88, 95% CI [0.85, 0.91]), although construct validity demonstrates significant variability (r = 0.72, 95% CI [0.67, 0.77]). Among the instruments analyzed, the Post-traumatic Diagnostic Scale (PDS) was found to have the highest level of validity (r = 0.83, p < 0.001), followed by the Clinician-Administered PTSD Scale for DSM-5 (CAPS-5) with r = 0.79 (p < 0.001), and the PTSD Checklist for DSM-5 (PCL-5) with r = 0.76 (p < 0.001). Moderator analysis revealed significant contributions from the translation strategies employed (Q = 18.42, p < 0.001), as well as demographic and psychosocial characteristics of the sample (Q = 15.67, p < 0.01), to fluctuations in instrument validity. When compared to the findings of Alqahtani et al. (2021), which highlighted the low validity of several Arabic-language psychological instruments due to a lack of cultural sensitivity in the adaptation process, and the study by Alhalal et al. (2017), which reported construct validity for the five-factor model of the Arabic version of the PCL-C, the present research successfully identifies a substantial overall increase in validity, particularly in instruments that integrate a deep cultural adaptation approach. Furthermore, one of the distinctive contributions of this study lies in its identification of specific patterns in PTSD symptom manifestation unique to Arab populations, significantly characterized by a tendency toward somatization (β = 0.45, p < 0.001) and the expression of distress in collective forms (β = 0.38, p < 0.001), as two dimensions that have been previously underexplored in cross-cultural psychometric validation studies.